Influence of the pandemic on the best romanian handball leagues for seniors - Varzaru, C.; Tudor, V. (Physical Education, Sport and Kinetotherapy Journal, 2021)
The current paper aims to present the situation of COVID-19 cases recorded among the teams participating in Liga Florilor MOL and Liga Zimbrilor (the best senior leagues in Romania), the monthly distribution of the number of no-shows due to coronavirus and the analysis of teams` adaptability to the new anti-COVID-19 regulations as regards the number of sanctions received for non-compliance with these rules. The novel coronavirus affected all teams participating in Liga Florilor MOL and Liga Zimbrilor. In total, 365 people including players and staff were infected with SARS CoV-2 during this season. Eight teams were in the situation of not being able to participate in handball tournaments, and 24 games were decided at the green table due to COVID-19, meaning 5.86% of the total number of games scheduled for the best men`s and women`s leagues in the 2020-2021 season. The Romanian Handball Federation organized 207 "bubble system" tournaments for all competitive categories, of which 31 were organized for Liga Florilor MOL (17) and Liga Zimbrilor (14). Throughout the season, the teams successfully adapted to the new rules against the spread of the SARS CoV-2 virus. The sanctions imposed for non-compliance with these rules, excepting the games ended 10:0, were extremely low in numbers. A single pecuniary penalty was applied, which was doubled by an exclusion from that tournament. In addition, a single warning was given to a team that violated the ban on using the locker room inside the sports hall.